2023
DOI: 10.9734/ijecc/2023/v13i113154
|View full text |Cite
|
Sign up to set email alerts
|

Sowing Time and Spacing Influenced Yield, Quality and Economics of Bt Cotton (Gossypium hirsutum L.)

P. M. Patel,
K. K. Patel,
C. K. Patel

Abstract: A field study was conducted in the 2019 kharif season at the Agronomy Instructional Farm, SDAU, SKNagar, Gujarat, India. To investigate that the sowing time and spacing influenced yield, quality and economics of Bt cotton (Gossypium hirsutum L.) in loamy sand soil. Twelve treatment combinations were examined, involving three sowing times (T1: 3rd week of May, T2: 1st week of June, T3: 3rd week of June) and four plant spacings (S1: 90 cm × 60 cm, S2: 90 cm × 45 cm, S3: 60 cm × 60 cm, S4: 60 cm × 45 cm). Four re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(12 reference statements)
1
0
0
Order By: Relevance
“…Similar observations of higher seed cotton and stalk yields at closer spacing compared to wider spacing was reported by Mahil and Loandhan [3]. Patel et al [5] reported higher seed cotton yield of Bt cotton with plant spacing of 45 cm × 30 cm than other plant spacing.…”
Section: Effect Of Spacingsupporting
confidence: 81%
“…Similar observations of higher seed cotton and stalk yields at closer spacing compared to wider spacing was reported by Mahil and Loandhan [3]. Patel et al [5] reported higher seed cotton yield of Bt cotton with plant spacing of 45 cm × 30 cm than other plant spacing.…”
Section: Effect Of Spacingsupporting
confidence: 81%